Effect of Dry Oxidation and Thermal Annealing on AlN/GaN/AlN/Si (111) and Evaluation of its Electrical Characteristics - Mohd Yusoff, Mohd Zaki; Mahyuddin, Azzafeerah; Hasssan, Zainuriah; Yahya, ‪Muhammad Syarifuddin (UI Scholars Hub, 2021)
We proposed a technique for improving the platinum (Pt) Schottky contact dark current of the AlN/GaN/AlN/Si(111) substrate. The AlN/GaN/AlN/ heterostructure sample was successfully grown on a silicon substrate by radio frequency molecular beam epitaxy. The high quality of the interlayer heterostructure sample was verified by transmission electron microscopy (TEM). From the TEM image, a good quality single interface layer with spacing less than 1 nm was detected. The strong significant peaks obtained by X-ray diffraction measurement indicated that the sample has a high structural quality for each grown layer. Dry oxidation and thermal annealing were used in conjunction to effectively reduce the leakage current of the Schottky contact of the AlN/GaN/AlN/Si(111) substrate. Energy-dispersive X-ray analysis revealed the presence of the element oxygen. Dry oxidation enhanced the surface roughness and surface-active area of the samples. Al2O3 contributed to the low leakage current of the Pt Schottky contact of the AlN/GaN/AlN/Si(111) substrate. The Al2O3 layer acted as an insulator layer, and retarded the current flow of devices.